Temperamental Dimensions in Early Childhood: Gender Differences and Their Relationship to Emotional and Behavioral Disorders in a Longitudinal Study - Navarro-Ariza, María Teresa; Infante-Cañete, Lidia; Madrid-Vivar, Dolores; Wallace-Ruíz, Agustín; Alarcón-Orozco, María Elena (MPDI, 2025)
Background: This longitudinal study aims to explore the stability and changes in child temperament dimensions between the ages of three and six, analyzing their relationship with emotional and behavioral problems, differentiated by gender. Method: This study involved 24 boys and 25 girls from various early childhood education centers in Málaga, Spain. To assess temperament, the Spanish adaptation of the Children’s Behavior Questionnaire was used, while emotional and behavioral problems were evaluated using the SPECI Screening for Emotional and Behavioral Problems in Children. Results: Findings indicate that 9 out of the 15 temperament dimensions remained stable, while 4—anger/frustration, attentional focusing, perceptual sensitivity, and sadness—showed significant changes in the total sample. The gender-specific analysis revealed different developmental patterns for boys and girls. Girls exhibited changes in attentional focusing, fear, and perceptual sensitivity, while boys showed changes in anger/frustration and attentional focusing. In addition, girls scored higher in discomfort and fear, whereas boys stood out in activity levels. Regarding behavioral problems, girls’ externalizing symptoms were significantly associated with attentional focusing and smiling/laughter, while internalizing symptoms were linked to low-intensity pleasure and perceptual sensitivity. Conclusions: These findings highlight the importance of addressing temperament from a gender-differentiated perspective when designing educational and family interventions aimed at promoting socioemotional development.
Keywords: Temperamento; Niños; Temperament; Gender; Internalizing; Externalizing; Stability; Change